2010
DOI: 10.1111/j.1752-7325.2010.00180.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating determinants of dentist productivity: new evidence

Abstract: Objectives Productivity (output per unit of input) is a major driver of dental service capacity. This study uses 2006-2007 data to update available knowledge on dentist productivity. Methods In 2006-2007 the authors surveyed 1,604 Oregon general dentists regarding. hours worked, practice size, payment and patient mix, prices, dentist visits, and dentist characteristics. Effects of practice inputs and other independent variables on productivity were estimated by multiple regression and path analysis. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 9 publications
1
18
0
1
Order By: Relevance
“…The latest work published by Conrad et al . is consistent with previously published work and showed that dentist productivity is influenced by dentist hours worked, number of assistants, number of operatories, number of hygienists, practice ownership, and the dentist's years of experience. Furthermore, Conrad et al .…”
Section: Introductionsupporting
confidence: 92%
See 4 more Smart Citations
“…The latest work published by Conrad et al . is consistent with previously published work and showed that dentist productivity is influenced by dentist hours worked, number of assistants, number of operatories, number of hygienists, practice ownership, and the dentist's years of experience. Furthermore, Conrad et al .…”
Section: Introductionsupporting
confidence: 92%
“…This allowed us to construct models with excellent explanatory power and to substantiate the work by Lam et al (2), which demonstrated that the dental assistant-to-provider ratio was the most significant factor affecting a dental clinic's productivity. We achieved a better model fit than Conrad et al (10), possibly because they evaluated the outcome variable of dentist visits per week, whereas we were able to focus on a clinics' total practice output, measured in relative value units. The strength of using relative value units as an output measure is that it reflects the time and complexity of the procedures being completed.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations